Financial vulnerability and monetary policy - Tobias Adrian; Fernando Duarte (Federal Reserve Bank of New York, 2016)
We present a parsimonious New Keynesian model that features financial vulnerabilities. The vulnerabilities generate time varying downside risk of GDP growth by driving the dynamics of risk premia. Monetary policy impacts the output gap directly via the IS curve, and indirectly via its impact on financial vulnerabilities. The optimal monetary policy rule always depends on financial vulnerabilities in addition to output, inflation, and the real rate. We show that a classic Taylor rule exacerbates downside risk of GDP growth relative to an optimal Taylor rule, thus generating welfare losses associated with negative skewness of GDP growth.
Keywords: G10; G12; E52; 330; monetary policy; macro-finance; financial stability